Transportation systems for tourism - Dileep, M. R. (Advances in spatial science)
"This textbook provides a comprehensive learning resource material for tourism transportation. Exploring the interrelationship between transport and tourism, it demonstrates how different types of transportation systems interact and are combined within the tourism destination framework. It addresses topics such as the geographical aspects of tourism transportation, technological advances in transportation, public transportation in tourism, drive tourism, recreational transportation, and various forms of tourism, including car, rail, coach, water, cycling, and space tourism. Readers will also learn about sustainability aspects, consumer behavior, and tourist behavior modelling. The book offers a valuable asset for graduate as well as master degree students in regional and spatial science, transportation engineering, and tourism and transportation economics, as well as for professionals in the travel, tourism, transport, and hospitality industries who are interested in the link between tourism and transportation, its benefits and impacts. Tourist destinations can strategically use this learning resource to gain a better understanding of the leisure and recreational aspects of the transportation system and consequently boost their appeal to tourists." --